Teaching primary physical education - Lawrence, Julia Clare (London SAGE, 2018)
Physical education is an important part of the primary curriculum and one that provides unique challenges for those involved with its teaching. This book offers a balanced and comprehensive overview of the subject, covering issues such as safe practice in PE, inclusion, subject leadership and cross-curricular approaches supported by an accessible theory-informed approach. This second edition includes: links to the new National Curriculum in England, each chapter mapped against the Teachers' Standards, a new chapter on physical literacy and development in the early years and primary ages, a new chapter on health-focused education and the contribution of PE, added case studies in every chapter, enhanced coverage of assessment in PE.
Why physical education? -- How pupils learn and develop -- Appraoaches to the teaching of physical education -- Inclusion in physical education -- Safe practice in physical education -- Developing motor competences -- Developing knowledge, skills and understanding across areas of activity -- Planning the learning experience -- Promoting physical education across the curriculum -- Physical education and the wider community -- Subject leadership in physical education
Includes bibliographical references and index.
Keywords: Physical education for children -- Great Britain; Elementary school teaching -- Great Britain; Physical education and training -- Safety measures; Elementary school teaching